Basin‐Scale Irrigation Planning in Areas with Scarce Data†. (21st June 2016) - Masumoto, Takao; Yoshida, Takeo; Kudo, Ryoji
Abstract: This paper presents a basin‐scale approach to irrigation planning for use in areas with scarce hydrological and meteorological data. We review the past development of cascade irrigation facilities in Cambodia's Kep Province and present the results of applying a distributed water circulation model that incorporates agricultural water use in Cambodia's Pursat River Basin. Basic hydrological and meteorological data are scarce for these areas, partly as a result of the Cambodian civil war. Although 70% of overall water use is for agriculture, irrigation rates in many areas of monsoonal Asia are low and farming depends mainly on rainwater, even in basins where paddy fields are dominant and water resources are abundant. Moreover, basic hydrological and meteorological data are scarce in these areas. Past irrigation planning proposals in these areas have not specified the required volumes of water or the necessary capacities of irrigation facilities. Our consideration of irrigation projects in the Pursat River Basin, based on meteorological data inputs estimated by using a general circulation and/or climate change model, showed that basin‐scale irrigation planning can be applied despite the scarcity of data. Application of the results of long‐term climate change modelling by Japan's Meteorological Research Institute and a distributed water circulation model developed by Institute for Rural Engineering, NARO (NIRE), show that it is possible to model and use basic data when observational data are inadequate. Copyright © 2016 John Wiley & Sons, Ltd.